THE EFFECT OF WORK MOTIVATION, COMMUNICATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE ON PT. JNE EXPRESS BENGKULU (Case Study of PT. JNE Express Bengkulu) - I Gede Sena Winaya; Ade Tiara Yulinda; Islamuddin; Asep Indra Gunawan (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
The title of this research is The Effect of Work Motivation, Communication and Work Discipline on Employees at PT JNE Express Bengkulu.  This study aims to analyze the effect of work motivation, communication, and work discipline on employee performance at PT. JNE Express Bengkulu. Quantitative methods were used with a sample of 55 employees, and data were collected through questionnaires and analyzed by multiple linear regression to determine the relationship between the variables studied.The results showed that work motivation, effective communication, and work discipline have a positive and significant influence on employee performance. Employees who are motivated, communicate well, and are disciplined tend to have better performance compared to employees who have low work motivation. In addition, effective communication is also proven to have a positive influence on employee performance. Overall, this study concludes that work motivation, communication, and work discipline together have a significant impact on employee performance. These findings provide practical recommendations for company management to improve performance through increased motivation, communication, and work discipline